A PECVD preparation process for optical film and optical film prepared therefrom

By adopting a multi -layer membrane structure process with specific sequence and thickness in PECVD technology, the problem of large internal stress and low binding force between the membrane layers has been solved, and the preparation of high -performance optical film is achieved. Long life.

CN119162562BActive Publication Date: 2025-01-28SHENZHEN FORBEST OPTOELECTRONIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411677512.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-28
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

When the existing PECVD technology deposits multilayer film structures, the internal stress between the film layers is large and the binding force is not high, which limits its application in the preparation of high-performance optical films.

Method used

The PECVD preparation processes of SIOX layers, SINX layers, SIOXNY layers, and SIOXFY layers with specific sequence arrangements and specific thickness, use the interference between multi -layer membrane structures, reduce the reflectivity of optical film, and optimize the various membrane layers of each membrane layer. Coating parameters to improve the combination and stability between the membrane layer.

Benefits of technology

The optical film is performed in the excellent transmission of 450-530nm, 600-700nm, and 1000-1200nm wavelength range, and improved the combination and stability between the membrane layers, extending the life of the optical film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a PECVD preparation process for an optical film and the optical film prepared therefrom, and relates to the field of optical film preparation. The PECVD preparation process for an optical film includes substrate preheating, deposition of SiO x Layer, SiN deposition x Layer, deposited SiO x N y Layer, deposited SiO x F y Layer, repeated deposition of SiO x N y Layer and SiO x F y Layer 3-8 and repeated deposition of SiO x Layer and SiN x The present invention can reduce the reflectivity of the optical film, increase the transmittance of the optical film in the wavelength range of 450-530nm, 600-700nm and 1000-1200nm, effectively reduce the internal stress between the film layers, improve the overall bonding strength and stability of the optical film, and help obtain an optical film that takes both optical performance and stability into consideration by arranging the film layers in a specific order and with specific thicknesses and matching the coating parameters of each film layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optical film preparation, and in particular to a PECVD preparation process for an optical film and the optical film prepared therefrom. Background Art

[0002] Optical thin films are widely used in various optical systems to adjust the transmission characteristics of light. Currently, traditional optical thin film deposition methods mainly include evaporation, sputtering, physical vapor deposition, chemical vapor deposition, and plasma-enhanced chemical vapor deposition (PECVD). Each of these methods has advantages, but also has some limitations.

[0003] Plasma-enhanced chemical vapor deposition (PECVD) has been widely used in the field of optical thin film preparation due to its advantages such as fast deposition speed and strong controllability. However, existing PECVD technology still suffers from problems such as high internal stress between film layers and weak bonding strength when depositing multilayer film structures, which limits its application in the preparation of high-performance optical thin films. Summary of the Invention

[0004] In order to improve the problems of large internal stress and low bonding strength between multilayer optical films in the related art, the present application provides a PECVD preparation process for an optical film and the optical film prepared therefrom.

[0005] In the first aspect, the present application provides a PECVD process for preparing an optical film using the following technical solutions:

[0006] A PECVD preparation process for an optical thin film comprises the following steps:

[0007] S1. Preheating the substrate: Preheat the double-sided polished substrate to a vacuum degree of 3.5*10 -4 Pa-4.0*10 -4 Pa, preheat in a chamber at 100-105°C for 10-20 minutes;

[0008] S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow ratio of SiH4 to N2O is 1:(1.0-1.2), the RF power is controlled at 200-250W, the reaction pressure is controlled at 20-30Pa, and the deposition thickness is 25-35nm;

[0009] S3, depositing SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow ratio of SiH4 to N2 is 1: (1.0-1.2), the RF power is controlled at 200-250W, the reaction pressure is controlled at 20-30Pa, and the deposition thickness is 10-15nm;

[0010] S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, and introduce SiH4, N2O and N2 into the chamber. The flow ratio of SiH4, N2O and N2 is (4-8):1:(4-8), the RF power is controlled at 200-250W, the reaction pressure is controlled at 20-30Pa, and the deposition thickness is 135-155nm;

[0011] S5, deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, and introduce SiH4, N2O and C2F6 into the chamber. The flow ratio of SiH4, N2O and C2F6 is (4-8): (4-8): 1, the RF power is controlled at 200-250W, the reaction pressure is controlled at 20-30Pa, and the deposition thickness is 80-90nm;

[0012] S6, repeat steps S4 and S5 3-8 times in sequence;

[0013] S7. Repeat steps S2 and S3 once to obtain an optical film.

[0014] In this application, the present invention arranges SiO in a specific order and with a specific thickness. x layer, SiN x layer, SiO x N y layer, SiO x F y By combining the layers and the coating parameters of each film layer, the interference cancellation effect between the multi-layer film structure is utilized to reduce the reflectivity of the optical film, resulting in excellent transmittance in the wavelength ranges of 450-530nm, 600-700nm, and 1000-1200nm. In addition, the optical film of this application has low internal stress and high bonding strength between the film layers, which can effectively improve the overall bonding strength and stability of the optical film and extend the service life of the optical film.

[0015] Among them, the substrate is first polished and preheated to provide a good foundation for the deposition of subsequent film layers, which is beneficial to improving the bonding strength between the film layer and the substrate, thereby improving the overall stability of the optical film.

[0016] Pre-deposit SiO on the substrate x layer, as a substrate with SiN x The transition layer between layers can improve the SiN x The stress difference between the layer and the substrate prevents the film from cracking and peeling due to excessive stress. It also helps to improve the adhesion between the film layers, thereby enhancing the overall stability of the optical film.

[0017] At the same time, by coordinating the coating parameters of each film layer, the reflectivity of the optical film can be reduced, the transmittance of the optical film in the wavelength range of 450-530nm, 600-700nm and 1000-1200nm can be increased, and the internal stress between the film layers can be effectively reduced, thereby improving the overall bonding strength and stability of the optical film, which is conducive to obtaining an optical film that takes into account both optical performance and stability.

[0018] SiN x As the surface layer of the optical film, SiN x It has excellent hardness and wear resistance, which can effectively prevent scratches on optical films and help extend the service life of optical films.

[0019] In some specific embodiments, the SiO x N y When the layer is formed, the flow ratio of SiH4, N2O and N2 is (5-5.5):1:(4.2-4.5).

[0020] In this application, the deposited SiO x N y When forming the optical film, the flow ratio of SiH4, N2O and N2 is further preferably (5-5.5):1:(4.2-4.5), which is beneficial to further improve the transmittance of the optical film in the wavelength range of 450-530nm, and at the same time is beneficial to further improve the thickness uniformity of the optical film.

[0021] In some specific embodiments, the SiO x F y When the layer is formed, the flow ratio of SiH4, N2O and C2F6 is (5-5.5): (4.8-5.2):1.

[0022] In this application, the deposited SiO x F yWhen forming the optical film, the flow ratio of SiH4, N2O and C2F6 is further preferably (5-5.5): (4.8-5.2): 1, which is beneficial to further improve the transmittance of the optical film in the wavelength range of 450-530nm, and at the same time is beneficial to further improve the thickness uniformity of the optical film.

[0023] In some specific embodiments, in step S2, the flow rate of SiH4 is controlled to be 70-75 sccm, in step S3, the flow rate of SiH4 is controlled to be 70-75 sccm, in step S4, the flow rate of N2O is controlled to be 15-20 sccm, and in step S5, the flow rate of C2F6 is controlled to be 15-20 sccm.

[0024] In the present application, by controlling the gas flow rate in each step within the above range, it is possible to achieve a faster deposition rate and ensure the deposition flatness of each film layer and the bonding strength between the film layers, which is beneficial to improving the thickness uniformity and structural stability of the optical film.

[0025] In some specific embodiments, in step S6, steps S4 and S5 are repeated 4-5 times in sequence.

[0026] In the present application, when steps S4 and S5 are repeated 4-5 times in sequence, the transmittance of the obtained optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm reaches more than 90%, and the optical performance of the optical film is further improved.

[0027] In some specific embodiments, the SiO x The layer was deposited to a thickness of 28-30 nm.

[0028] In this application, SiO is further preferred. x The deposition thickness of the layer is 28-30nm, which can further reduce the SiN x layer and substrate or SiO x F y The stress between the layers is reduced, thereby further improving the bonding strength between the optical film layers.

[0029] In some specific embodiments, the SiN x The layer was deposited to a thickness of 10-12 nm.

[0030] In this application, SiN is further preferred. x The deposition thickness of the layer is 10-12 nm, which can obtain a scratch-resistant optical film while obtaining an optical film with good light transmittance.

[0031] In some specific embodiments, the SiO x Ny The deposition thickness of the layer is 140-145 nm, and the SiO x F y The deposited layer thickness was 84.5-86.5 nm.

[0032] In this application, SiO is further preferred. x N y The deposition thickness of the layer is 140-145nm, SiO x F y The deposition thickness of the layer is 84.5-86.5 nm, which is beneficial to further improve the transmittance of the optical film in the wavelength ranges of 450-530 nm, 600-700 nm and 1000-1200 nm.

[0033] In some specific embodiments, the substrate is any one of a polymethyl methacrylate substrate, a polycarbonate substrate, and a polystyrene substrate.

[0034] In a second aspect, the present application provides an optical film produced by the PECVD preparation process of any of the above-mentioned optical films.

[0035] In summary, this application has at least the following beneficial technical effects:

[0036] (1) In this application, the SiO2 is arranged in a specific order and with a specific thickness. x layer, SiN x layer, SiO x N y layer, SiO x F y By combining the layers and the coating parameters of each film layer, the interference cancellation effect between the multi-layer film structure is utilized to reduce the reflectivity of the optical film, resulting in excellent transmittance in the wavelength ranges of 450-530nm, 600-700nm, and 1000-1200nm. In addition, the optical film of this application has low internal stress and high bonding strength between the film layers, which can effectively improve the overall bonding strength and stability of the optical film and extend the service life of the optical film.

[0037] (2) In the present application, when steps S4 and S5 are repeated 4-5 times in sequence, the transmittance of the obtained optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm is more than 90%, and the optical performance of the optical film is further improved. DETAILED DESCRIPTION

[0038] The present application is further described below with reference to specific experiments. The optical films in the embodiments and comparative examples of the present application are prepared using a PECVD-1201 plasma enhanced chemical vapor deposition system, but the system is not limited to this equipment. Example

[0039] [Example 1]

[0040] An optical film is prepared using a PECVD preparation process. The specific PECVD preparation process includes the following steps:

[0041] S1. Preheating the substrate: Preheat the double-sided polished polymethyl methacrylate substrate to a vacuum degree of 3.5*10 -4 Pa, preheated in a chamber at 100°C for 20 min;

[0042] S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow rate of SiH4 is controlled to 45 sccm, the flow ratio of SiH4 to N2O is 1:1, the RF power is controlled to 200 W, the reaction pressure is controlled to 30 Pa, and the deposition thickness is 25 nm;

[0043] S3, depositing SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2 is 1:1, the RF power is controlled to 200W, the reaction pressure is controlled to 30Pa, and the deposition thickness is 10nm;

[0044] S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow rate of N2O is controlled to 10 sccm, the flow ratio of SiH4, N2O and N2 is 4:1:4, the RF power is controlled to 200 W, the reaction pressure is controlled to 30 Pa, and the deposition thickness is 135 nm;

[0045] S5, deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and C2F6 into the chamber, the flow rate of C2F6 is controlled to 10 sccm, the flow ratio of SiH4, N2O and C2F6 is 4:4:1, the RF power is controlled to 200 W, the reaction pressure is controlled to 30 Pa, and the deposition thickness is 80 nm;

[0046] S6, repeat steps S4 and S5 three times;

[0047] S7. Repeat steps S2 and S3 once to obtain an optical film.

[0048] [Example 2]

[0049] An optical film is prepared using a PECVD preparation process. The specific PECVD preparation process includes the following steps:

[0050] S1. Preheating the substrate: Preheat the double-sided polished polymethyl methacrylate substrate to a vacuum degree of 4.0*10 -4 Pa, preheated in a chamber at 105°C for 10 min;

[0051] S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow rate of SiH4 is controlled to 45 sccm, the flow ratio of SiH4 to N2O is 1:1.2, the RF power is controlled to 250 W, the reaction pressure is controlled to 20 Pa, and the deposition thickness is 35 nm;

[0052] S3, depositing SiN x Layer: vacuum the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow rate of SiH4 is controlled to 45sccm, the flow ratio of SiH4 to N2 is 1:1.2, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 15nm;

[0053] S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow rate of N2O is controlled to 10sccm, the flow ratio of SiH4, N2O and N2 is 8:1:8, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 155nm;

[0054] S5, deposition of SiO x F y Layer: Evacuate the chamber to 9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and C2F6 into the chamber, the flow rate of C2F6 is controlled to 10sccm, the flow ratio of SiH4, N2O and C2F6 is 8:8:1, the RF power is controlled to 250W, the reaction pressure is controlled to 20Pa, and the deposition thickness is 90nm;

[0055] S6, repeat steps S4 and S5 8 times in sequence;

[0056] S7. Repeat steps S2 and S3 once to obtain an optical film.

[0057] [Example 3]

[0058] An optical film, which differs from [Example 1] in that: in step S4, the flow ratio of SiH4, N2O and N2 is 5:1:4.5.

[0059] [Example 4]

[0060] An optical film, which differs from [Example 1] in that: in step S4, the flow ratio of SiH4, N2O and N2 is 8:1:8.

[0061] [Example 5]

[0062] An optical film, which differs from [Example 3] in that: in step S5, the flow ratio of SiH4, N2O and C2F6 is 5:5:1.

[0063] [Example 6]

[0064] An optical film, which differs from [Example 3] in that: in step S5, the flow ratio of SiH4, N2O and C2F6 is 8:8:1.

[0065] [Example 7]

[0066] An optical film, which differs from [Example 5] in that: in step S2, the flow rate of SiH4 is controlled to 70sccm, in step S3, the flow rate of SiH4 is controlled to 70sccm, in step S4, the flow rate of N2O is controlled to 18sccm, and in step S5, the flow rate of C2F6 is controlled to 18sccm.

[0067] [Example 8]

[0068] An optical film, which differs from [Example 5] in that: in step S2, the flow rate of SiH4 is controlled to 85sccm, in step S3, the flow rate of SiH4 is controlled to 85sccm, in step S4, the flow rate of N2O is controlled to 25sccm, and in step S5, the flow rate of C2F6 is controlled to 25sccm.

[0069] [Example 9]

[0070] An optical film, which differs from [Example 7] in that: in step S6, steps S4 and S5 are repeated five times in sequence.

[0071] [Example 10]

[0072] An optical film, which differs from [Example 7] in that: in step S6, steps S4 and S5 are repeated 8 times in sequence.

[0073] [Example 11]

[0074] An optical film, which differs from [Example 9] in that: SiO x The deposition thickness of the layer is 30nm, SiN x The deposition thickness of the layer is 10 nm, SiO x N y The deposition thickness of the layer is 142nm, SiO x F y The layer was deposited to a thickness of 85 nm.

[0075] [Example 12]

[0076] An optical film, which differs from [Example 9] in that: SiO x The deposition thickness of the layer is 35nm, SiN x The deposition thickness of the layer is 15 nm, SiO x N y The deposition thickness of the layer is 155 nm, SiO x F y The layer was deposited to a thickness of 90 nm.

[0077] Comparative Example

[0078] [Comparative Example 1]

[0079] An optical film, which differs from [Example 1] in that step S6 is omitted.

[0080] [Comparative Example 2]

[0081] An optical film, which differs from [Example 1] in that: in step S6, steps S4 and S5 are repeated 10 times in sequence.

[0082] [Comparative Example 3]

[0083] An optical film, which differs from [Example 1] in that: the substrate and SiN x SiO between layers x layer.

[0084] Performance testing

[0085] (1) Transmittance: The transmittance of the optical films in the embodiments and comparative examples was tested within the wavelength ranges of 450-530 nm, 600-700 nm, and 1000-1200 nm, and the minimum and maximum transmittance within each wavelength range were recorded.

[0086] (2) Thickness non-uniformity: The optical films in the examples and comparative examples were cut into samples with a size of 200 mm * 200 mm * 200 mm. The thickness was measured at 9 locations on the samples at equal intervals. The thickness non-uniformity of the optical films was calculated. Thickness non-uniformity = (d max -d min ) / d avg

[0087] , in this formula, d max represents the maximum thickness in the sample, d min represents the minimum thickness in the sample, d avg Represents the average thickness of 9 locations. The smaller the thickness non-uniformity, the better the thickness uniformity of the optical film.

[0088] (3) Film bonding strength: The test was conducted according to Section 7 of GB / T 26332.4-2015. The tape was pulled up at a rate of 30 mm / s. The adhesion grade of the film was recorded according to the evaluation system in the standard. The lower the adhesion grade, the higher the bonding strength between the film layers.

[0089] Table 1 Light transmittance record table

[0090]

[0091] Table 2 Thickness non-uniformity and adhesion level record

[0092]

[0093] The difference between Comparative Examples 1 and 2 and Example 1 is that: SiO x N y layer, SiO x F y The number of layers is different. Among them, the SiO x N y layer, SiO x F y The number of layers is 1 layer each, and the SiO x N y layer, SiO x F y The number of layers is 11, and in Example 1, SiO x N y layer, SiO x F y The number of layers is 4, that is, SSiO x N y layer, SiO x F yThe number of layers is within the range of 4-9 layers defined in this application. The SiO x N y layer, SiO x F y The number of layers is not within the range defined in this application. Combining the test data in Tables 1-2, it can be seen that the thickness uniformity and adhesion strength between the optical films in Comparative Examples 1-2 are comparable to those in Example 1, but the transmittance of the optical films in Comparative Examples 1-2 in the wavelength ranges of 450-530nm, 600-700nm, and 1000-1200nm are all reduced.

[0094] The difference between Comparative Example 3 and Example 1 is that: Comparative Example 3 omits the x SiO between layers x Combined with the test data in Table 1-2, it can be seen that: omitting SiO x After the addition of the layers, the transmittance of the optical film in the wavelength ranges of 450-530nm, 600-700nm and 1000-1200nm decreased. At the same time, the adhesion level between the optical film layers increased, indicating that the bonding strength between the film layers decreased.

[0095] The difference between Example 3-4 and Example 1 is that in step S4 of Example 3, the flow ratio of SiH4, N2O, and N2 is within the range of (5-5.5):1:(4.2-4.5). Combined with the data in Table 1-2, it can be seen that the flow ratio of SiH4, N2O, and N2 is within the range of (5-5.5):1:(4.2-4.5), which is beneficial for further improving the transmittance of the optical film in the wavelength range of 450-530nm.

[0096] The difference between Example 5-6 and Example 3 is that in step S5 of Example 5, the flow ratio of SiH4, N2O, and C2F6 is within the range of (5-5.5):(4.8-5.2):1. Combined with the test data in Table 1-2, it can be seen that the flow ratio of SiH4, N2O, and C2F6 within the range of (5-5.5):(4.8-5.2):1 is beneficial for further improving the transmittance of the optical film in the wavelength range of 450-530nm.

[0097] The difference between Example 7-8 and Example 5 is that in Example 7, the flow rate of SiH4 is controlled within the range of 70-75 sccm, in step S3, the flow rate of SiH4 is controlled within the range of 70-75 sccm, in step S4, the flow rate of N2O is controlled within the range of 15-20 sccm, and in step S5, the flow rate of C2F6 is controlled within the range of 15-20 sccm. Combined with the test data in Table 1-2, it can be seen that, with other conditions unchanged, controlling the flow rates of each gas within the above ranges further improves the optical properties of the optical film, as well as the thickness uniformity and interlayer bonding strength of the film.

[0098] The difference between Examples 9-10 and Example 7 lies in the number of repetitions of steps S4 and S5. In Example 9, steps S4 and S5 were repeated 4-5 times. Combined with the test data in Tables 1-2, it can be seen that when steps S4 and S5 were repeated 4-5 times, the transmittance of the resulting optical film reached over 90% in the wavelength ranges of 450-530 nm, 600-700 nm, and 1000-1200 nm, further improving the optical performance of the optical film.

[0099] The difference between Example 11-12 and Example 9 is that the thickness of each layer is inconsistent. x The deposition thickness of the layer is in the range of 28-30nm, SiN x The deposition thickness of the layer is in the range of 10-12 nm, and the SiO x N y The deposition thickness of the layer is in the range of 140-145 nm, and the SiO x F y The deposition thickness of the layer is within the range of 84.5-86.5 nm. Combining the test data in Table 1-2, it can be seen that the thickness of each layer is further preferably within the above range, which is conducive to further improving the transmittance of the optical film in the wavelength ranges of 450-530 nm, 600-700 nm and 1000-1200 nm.

[0100] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A PECVD preparation process for an optical thin film, characterized in that: The following steps are involved: S1. Preheating the substrate: Preheat the double-sided polished substrate in a vacuum of 3.5*10 -4 Pa-4.0*10 -4 Pa, preheat in a chamber at 100-105°C for 10-20 min; S2, deposition of SiO x Layer: Stop evacuating the chamber, introduce SiH4 and N2O into the chamber, the flow ratio of SiH4 to N2O is 1:(1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 25-35nm; S3, deposition of SiN x Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4 and N2 into the chamber, the flow ratio of SiH4 to N2 is 1: (1.0-1.2), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 10-15nm; S4, deposition of SiO x N y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, introduce SiH4, N2O and N2 into the chamber, the flow ratio of SiH4, N2O and N2 is (4-8): 1: (4-8), the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 135-155nm; S5. Deposition of SiO x F y Layer: Evacuate the chamber to 9.4*10 -3 Pa-9.8*10 -3 Pa, then stop vacuuming, and introduce SiH4, N2O and C2F6 into the chamber. The flow ratio of SiH4, N2O and C2F6 is (4-8): (4-8): 1, the RF power is controlled to 200-250W, the reaction pressure is controlled to 20-30Pa, and the deposition thickness is 80-90nm; S6, repeat steps S4 and S5 3-8 times in sequence; S7. Repeat steps S2 and S3 once to obtain an optical film.

2. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: Deposition of SiO x N y When the layer is formed, the flow ratio of SiH4, N2O and N2 is (5-5.5):1:(4.2-4.5).

3. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: Deposition of SiO x F y When the layer is formed, the flow ratio of SiH4, N2O and C2F6 is (5-5.5): (4.8-5.2):

1.

4. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: In step S2, the flow rate of SiH4 is controlled to be 70-75sccm, in step S3, the flow rate of SiH4 is controlled to be 70-75sccm, in step S4, the flow rate of N2O is controlled to be 15-20sccm, and in step S5, the flow rate of C2F6 is controlled to be 15-20sccm.

5. The PECVD preparation process for an optical thin film according to claim 1, characterized in that: In step S6, steps S4 and S5 are repeated 4-5 times in sequence.

6. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiO x The layer was deposited with a thickness of 28-30 nm.

7. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiN x The layer was deposited with a thickness of 10-12 nm.

8. The PECVD process for preparing an optical thin film according to claim 1, characterized in that: The SiO x N y The deposition thickness of the layer is 140-145 nm. x F y The deposited layer thickness was 84.5-86.5 nm.

9. A PECVD process for preparing an optical thin film according to any one of claims 1 to 8, characterized in that: The substrate is any one of a polymethyl methacrylate substrate, a polycarbonate substrate and a polystyrene substrate.

10. An optical film, characterized in that: The optical film is prepared by the PECVD preparation process of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing solar cell laminated antireflective film through tubular PECVD

    CN103943717A

  • Structured multilayer optical film with self-focusing function and production method thereof

    CN110850514A